PLAGIARISM IN ACADEMIC TEXTS LEGAL AND ETHICAL ISSUES - Sobirova, Nozimakhon (International Journal of Business, Law and Political Science, 2024)
Plagiarism in academic texts poses significant challenges to the integrity of scholarly work and the ethical standards of academia. While academic institutions have developed extensive policies to address plagiarism, the legal and ethical implications continue to evolve with advancements in digital technology and access to information. There is a need for a comprehensive analysis that integrates the legal frameworks and ethical considerations surrounding plagiarism, particularly in the context of emerging digital practices. This study aims to examine the legal and ethical dimensions of plagiarism in academic texts, evaluating current practices, enforcement mechanisms, and their effectiveness in maintaining academic integrity. The research reveals that while legal measures and institutional policies have improved, inconsistencies in enforcement and evolving digital contexts present ongoing challenges. This study offers a unique perspective by integrating legal and ethical analyses with practical implications for academic institutions, providing a holistic view of how plagiarism issues are managed and perceived. The findings underscore the necessity for continuous updates to plagiarism policies and enforcement strategies, advocating for enhanced educational efforts to promote academic integrity and address the complexities introduced by digital technologies.